Commensal-to-pathogen transition: One-single transposon insertion results in two pathoadaptive traits in Escherichia coli -macrophage interaction - João T. Proença (Nature Portfolio, 2017)
Abstract Escherichia coli is both a harmless commensal in the intestines of many mammals, as well as a dangerous pathogen. The evolutionary paths taken by strains of this species in the commensal-to-pathogen transition are complex and can involve changes both in the core genome, as well in the pan-genome. One way to understand the likely paths that a commensal strain of E. coli takes when evolving pathogenicity is through experimentally evolving the strain under the selective pressures that it will have to withstand as a pathogen. Here, we report that a commensal strain, under continuous pressure from macrophages, recurrently acquired a transposable element insertion, which resulted in two key phenotypic changes: increased intracellular survival, through the delay of phagosome maturation and increased ability to escape macrophages. We further show that the acquisition of the pathoadaptive traits was accompanied by small but significant changes in the transcriptome of macrophages upon infection. These results show that under constant pressures from a key component of the host immune system, namely macrophage phagocytosis, commensal E. coli rapidly acquires pathoadaptive mutations that cause transcriptome changes associated to the host-microbe duet.